Studies on Dye Decolorization by Ultrasound Assisted Electrocoagulation. Issue 3 (14th December 2015) - Vianney, Mujyambere Jean Marie; Muthukumar, Karuppan
Abstract : This study presents the removal of azo dyes (Congo red, Methyl red, and Eriochrome black T) from aqueous solutions by ultrasound assisted electrocoagulation (UE). In this method, dye solutions were simultaneously sonicated and electrolyzed. The effect of various operating parameters such as intensity of irradiation, pH, current intensity, initial concentration of the dye, and temperature on the performance of the process was investigated. The reduction in chemical oxygen demand, biological oxygen demand, hardness, and alkalinity were assessed. The kinetic analysis of the data showed a pseudo‐first order degradation for all three dyes. The results showed that UE is an effective method for the destruction of dyes. Abstract : Aqueous solution containing Congo red, Methyl red, and Eriochrome black T were decolorized by ultrasound assisted electrocoagulation. This method was found to be an efficient process which also showed faster decolorization compared to electrocoagulation and ultrasound. The influence of current and irradiation intensity, temperature, and nature of electrodes were investigated.